Analysis of risk factors for bladder neck contracture after transurethral endoscopic surgery for benign prostatic hyperplasia - Yingbing Wu; Lei Huang; Can Liu; Shujun Bai; Yu Chen; Qiong Bao; Xing Luo; Jingzhen Zhu; Weihua Fu; Ji Zheng; Zhao Jiang; Bishao Sun (The Aging Male)
Objective To investigate the risk factors of bladder neck contracture (BNC) after transurethral endoscopic surgery for benign prostatic hyperplasia (BPH), and to provide a reference basis for the clinic.Methods Clinical data of patients who underwent transurethral endoscopic surgery in our hospital from December 2019 to May 2023 were retrospectively collected. The incidence and risk factors of BNC after transurethral endoscopic surgery were analyzed by multivariate logistic regression analysis.Results A total of 420 cases were included in this study, of which 246 were treated with bipolar transurethral resection of the prostate (bTURP) and 174 with green light laser vaporization of the prostate (GL-PVP), and there was no statistically significant difference in the incidence of BNC when comparing these two types of operations. A total of 18 patients developed BNC after surgery, and the overall incidence of BNC was 4.29%. Multivariate logistic regression analysis showed that smaller preoperative prostate volume (p = 0.042), smoking history (p = 0.009), positive preoperative urine culture (p = 0.001), and prolonged postoperative catheterization days (p = 0.003) were independent risk factors of BNC.Conclusion Smaller preoperative prostate volume, smoking history, positive preoperative urine culture, and prolonged postoperative indwelling catheterisation were independent risk factors for BNC.